1991
DOI: 10.1111/j.1365-2125.1991.tb05594.x
|View full text |Cite
|
Sign up to set email alerts
|

The activation of the biguanide antimalarial proguanil co‐segregates with the mephenytoin oxidation polymorphism‐a panel study.

Abstract: The activation of the antimalarial drug proguanil (PG) to the active metabolite cycloguanil (CG) has been evaluated in a panel of 18 subjects. These subjects had previously been screened and classified as mephenytoin poor (PMm) or extensive metabolisers (EMm) and sparteine poor (PMs) or extensive metabolisers (EMs). Five subjects had the phenotype PMm/EMs, one was PMm/PMs, six subjects were EMm/PMs and six were EMm/EMs. The PG/CG ratio in urine (8 h) was significantly higher in PMm than in EMm (P = 0.0013). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(74 citation statements)
references
References 24 publications
4
70
0
Order By: Relevance
“…Subsequent studies confirmed that S-mephenytoin hydroxylase is polymorphically expressed (Kupfer and Preisig, 1984;Wedlund et al, 1984) and that other drugs such as omeprazole and proguanil have metabolism that cosegregates with that of mephenytoin (Table 5) (Ward et al, 1991;Chang et al, 1995a). The ability of individuals to metabolize S-mephenytoin has enabled them to be classified as PMs or EMs.…”
Section: Cyp2c19mentioning
confidence: 87%
“…Subsequent studies confirmed that S-mephenytoin hydroxylase is polymorphically expressed (Kupfer and Preisig, 1984;Wedlund et al, 1984) and that other drugs such as omeprazole and proguanil have metabolism that cosegregates with that of mephenytoin (Table 5) (Ward et al, 1991;Chang et al, 1995a). The ability of individuals to metabolize S-mephenytoin has enabled them to be classified as PMs or EMs.…”
Section: Cyp2c19mentioning
confidence: 87%
“…Keywords CYP2C19, omeprazole, gender, Korean, Swedes [2] , proguanil [3] and proton pump inhibitors (PPIs) [4]. The major metabolites of omeprazole detected in vivo in human plasma are 5-hydroxyomeprazole formed by CYP2C19 and omeprazole sulphone formed by CYP3A4 [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…The assay had a lower limit of detection of 5 and 3 ng ml -1 and an inter-and intra-assay variability of <6% for proguanil and the metabolite cycloguanil, respectively. A proguanil : cycloguanil metabolic ratio of >10 corresponds to the PM phenotype [4].…”
Section: Methodsmentioning
confidence: 99%
“…CYP2C19 activity status was determined using the probe drug proguanil (200 mg) [4]. The metabolic ratio was calculated from the plasma concentrations of proguanil and its metabolite cycloguanil by HPLC analysis of a 3 h blood sample.…”
Section: Methodsmentioning
confidence: 99%